ANALISIS AGRIBISNIS TERNAK KAMBING DENGAN PENDEKATAN MARKET STRUCTURE CONDUCT AND PERFORMANCE DI KABUPATEN NGAWI - Erik Priyo Santoso; Eka Fitasari (BUANA SAINS, 2016)
This research has done on February 9th, 2019 to March 4th, 2009 in Ngawi regency. This research has an aim to identify marketing channel, marketing efficiency by using marketing margin analysis and market structure approachment, conduct and performance (MS-C-P) including marketing integration and Transmission elasticity of goat farming cost.This research used puposive sampling technique method and snowball sampling. The data collected by interviewing and observation. The data analysis are descriptive data analysis, marketing margin analysis, MS-C-P approahment analysis and market ing integration includes cost transmission elasticity.The results show that there are eight marketing channels, agribusiness analysis by using MS-C-P approachment shows that there are many factors which not efficient yet. The level of market integration between market at the level of farmer and market of the level low consumers, with coefficeint coreelation 0.945 (less than one) at the line I. At the line VI, the integration market is perfect because the correlation r = 1. The movemnet of consumers and farmers cost, looked from transmission elasticity cost 0, 00086 at the line I and line VI 0, 00077 means the speed of cost changes at breeder level is smaller than the speed of cost changes at retailer level.It concludes that structure influences conduct (lower the concentration-higher the competition at market). Conduct influences performance (higher the competition-lower the the market power/lower the advantage). Structure influences performance (lower the market concentration- higher the competition-lower the market power). There is an resiprok (interrelation) between S-C-P and P-C-S.It suggests that institutional formation and contract farming application to avoid market perfect competition and the using of telecenter as market information service.